Flame AAS determination of beryllium in water samples after preconcentration on activated carbon - Avci, Halim; Yaman, Mehmet (Atomic Spectroscopy Press Ltd, 2006)
A simple, sensitive, accurate, and selective method for the determination of ultratrace levels of beryllium is modified. The method is based on preconcentration of the complexes of beryllium-acetylacetone plus morin on activated carbon at pH 8.0-10.0 using a contact time as low as 10 minutes. The adsorbed beryllium was eluted with aqua regia and measured by flame atomic absorption spectrometry (FAAS). Recoveries up to 85% were achieved. For removing chemical interferences and applying the method to the Be determination in water samples, sensitivity and reproducibility were examined. The Be detection limit was found to be 0.012 ng mL(-1). The relative standard deviation (%RSD) was found to be 7% for 200 mL of 0.5 ng mL(-1) Be and 9% for 1000 mL of 0. 1 ng mL(-1) Be using the 10 replicate enrichment procedures. The Be concentrations in the water samples were found to be in the 0.05-1.687 ng mL(-1) range.
Keywords: Atomic-Absorption-Spectrometry; Solid-Phase Extraction; Spectrophotometric Determination; Trace Amounts; Drinking-Water; Enrichment; Lead; Vegetables; Vanadium; Matrices